Assessment of Potentially Inappropriate Medications Using the EU (7)-PIM List, in a Sample of Portuguese Older Adults' Residents in Nursing Homes - Plácido, Ana (2022)
Abstract: Prescription of potentially inappropriate medication (PIM) in older adults is associated with poor clinical outcomes. The EU (7)-PIM list was created for the European market to improve pharmacotherapy in older adults. Purpose: This work aims to characterize the medication profile and assess the presence of PIM, using the EU (7)-PIM list in older adults' residents at nursing homes. Methods: Retrospective data were collected from the anonymized nursing home records. After PIM identification, a descriptive analysis was performed, and a generalized linear model for dependent negative binomial-type variables was constructed to assess the risk of PIM. Results: Of the 210 participants (mean age 85.10), 82.40% were polymedicated. PIM was observed in 86.4% participants (mean per patient = 2.30± 0.10). The most common PIM were proton pump inhibitors (n = 121, 57.62%), followed by anxiolytics (n = 96, 45.71%). 64.30% of all patients take 2-4 PIM and 5.80% take five or more PIM. The occurrence of PIM is influenced by the number of prescribed medicines (RR 1.14; 95% CI 1.1.-1.17) and the presence of digestive system diseases (RR 1.05; 95% CI 1.0-1.09). Conclusion: The high prevalence of PIM observations highlights the necessity of the implementation of guidelines to prevent PIM.